PPARγ activation by pioglitazone enhances the anti-proliferative effects of doxorubicin on pro-monocytic THP-1 leukemia cells via inducing apoptosis and G2/M cell cycle arrest. (3rd September 2022) - Ghasemi, Hassan; Jamshidi, Ali; Ghatee, Mohammad Amin; Mazhab-Jafari, Komeil; Khorasani, Milad; Rahmati, Mina; Mohammadi, Saeed
Abstract: Purpose: Doxorubicin (DOX) is a common chemotherapeutic agent, with toxic side effects, and chemoresistance. Combination chemotherapy is a successful approach to overcome these limitations. Here, we investigated the effects of pioglitazone (PGZ), a PPARγ agonist, and/or DOX on the viability, cell cycle, apoptosis on THP-1 cells and normal human monocytes (NHMs). Methods: MTT assay was used to evaluate the cytotoxicity of DOX and/or PGZ. Cell cycle progression and apoptosis induction were examined by PI or Annexin V-PI double staining, and analyzed by flow cytometry. Quantitative RT-PCR was used to evaluate the changes in the mRNA expression of cell cycle progression or apoptosis-associated genes including P27, P21, CDK2, P53, BCL2 and FasR. Results: DOX, PGZ and DOX + PGZ exerted their cytotoxic effects in a dose- and time-dependent manner with low toxicity on NHMs. The cell growth inhibitory effects of DOX were in association with G2/M arrest, while PGZ executed S phase arrest. PGZ treatment enhanced G2/M among DOX-treated combinations with moderate elevation in the S phase. DOX, PGZ and combined treatments induced apoptosis (mostly late phase) in a dose-dependent manner. All treatments resulted in the significant overexpression of p21, p27, p53 and FasR genes and downregulation of CDK2. DOX + PGZ combined treatments exhibited the most significant changes in mRNA expression. Conclusion: We demonstrated that the antiproliferative, cell cycle regulation and apoptosis-inducing capacity of DOX was enhanced by PGZ in THP-1 leukemia cells in a dose-dependent manner. Therefore, the combination of DOX + PGZ could be used as a novel combination to target AML.